A qualitative investigation into the experience of burnout in Singaporean coaches - Ong, N. C. H.; Zhao, J. H. (Qualitative Research in Sport, Exercise and Health, 2019)
The purpose of this study was to investigate the phenomenon of burnout in the Singaporean coaching population. Semi-structured interviews were conducted with four Singaporean coaches with high burnout, and four coaches with low burnout. These coaches were identified using the cluster analysis results from an earlier study. Using interpretative phenomenological analysis to analyse the data, two main coach profiles emerged. The first profile comprised of factors that contributed to coach burnout, as well as the effects of burnout on the lives of coaches. The second profile comprised of factors and characteristics that protected coaches against burnout and helped them to thrive in their role. The two coach profiles were explored in greater depth, and key aspects that were unique to the Singaporean context were highlighted. These included financial struggles, limited facilities, monopolisation by big companies, inadequacy of coach training, dealing with students and parents, toxic coaching culture, perceived favouritism towards foreign coaches, and struggles of female coaches. Practical implications for coaches included inculcating a less outcome-orientated approach towards coaching, seeking good social support, engaging in regular self-care, and gaining more coaching experience